Computing Cutting Time in Turning Operation Based on AutoCAD Drawings. - Kassir, May George A.; AL-Khafaji, Mohanned Mohammed H.; Alwan, Hussam L. (Nahrain University College of Engineering Journal, 2019)
In view of importance the cutting time, it is considered one of the most important factors in different machining processes where it affects production time, cycle time, and product cost consequently. This research aims to build up a system for computing cutting time in turning operations from AutoCAD drawings. Theproposed system has been built using Visual Basic programming language and interfacing it with AutoCAD by Visual Basic for Application (VBA) Technique. The system is able to compute cutting time from the drawings according to the color of each solid entity; these colors were defined previously in the system.They are related to the type of turning operation (external, internal, and facing turning operations) as well as the rough andfinish machining operations. The system was examined with two models, and it was accurate and efficient. It is possible consideration theproposed system step toward the integration between CAPP/CAM systems